Influence of Drainage Layer Thickness on the Preconsolidation Rate of Dredged Marine Soils : A Lab Simulation - Siti Farhanah, SM Johan; Chan, Chee Ming (IOP Publishing Ltd, 2020)
This study conducted to investigate the improved consolidation rate of dredged marine soils used as backfills in land reclamation, with the aim of making the material’s reuse more favourable on site compared to disposal as in the normal practice. In order to quicken the dissipation of excess pore water under loading, efficiency of the drainage layers sandwiching the dredged marine soil plays an important role. With modification of a large oedometer, the present study examines the efficiency of three granular materials, i.e. sand (S), palm oil clinker (POC) and pavement milling waste (PMW) in two different drainage thicknesses for the effective discharge of pore water during consolidation of the dredged marine soils. With sand adopted as Control, it observed that thicker layers (100%) of the granular materials produced higher consolidation rates by 10% compared to 50% of thickness. Settlement reduction also found at POC and PMW as the drainage layers, i.e. 0.6% and 0.5% respectively in comparison with sand. Obviously, the improvement of DMS consolidation about 2% when implantation of granular layer.